Morphology and Beyond – A Rare Case of Metastatic Succinate Dehydrogenase-Deficient Paraganglioma of the Vulva - Sayali Prakash Kshirsagar; Ashwini Ratnakar; Manasi A. Gosavi (Annals of African Medicine, 2026)
Abstract Paragangliomas (PGLs) are uncommon neuroendocrine tumors of extra-adrenal origin, and involvement of the vulva is exceptionally rare, often creating diagnostic difficulty due to morphological overlap with other neoplasms. We report a case of 35-year-old female with a prior history of pheochromocytoma who presented with a vulvar mass. Histopathological examination showed a tumor composed of nests and trabeculae (Zellballen pattern) of cells with neuroendocrine features, closely simulating other nested tumors. Immunohistochemical (IHC) analysis revealed strong synaptophysin, chromogranin, and CD56 expression, while the tumor cells were negative for cytokeratin, Melan-A, and S100, thereby excluding epithelial, melanocytic, and sustentacular lineages. A key finding was the loss of Succinate dehydrogenase subunit B (SDHB) expression along with a markedly elevated Ki-67 index (~60%), indicating aggressive biological behavior and raising the possibility of an underlying hereditary syndrome, for which genetic counseling is recommended. Integrating the histopathological findings with clinical and radiological data led to a diagnosis of Metastatic PGL. This case emphasizes the importance of a comprehensive IHC approach in accurately classifying such rare and clinically significant tumors.